2023
DOI: 10.1002/ett.4739
|View full text |Cite
|
Sign up to set email alerts
|

A levy flight based strategy to improve the exploitation capability of arithmetic optimization algorithm for engineering global optimization problems

Abstract: The existing arithmetic optimization algorithm is a meta-heuristics algorithm that utilizes distribution behaviors for the different parameters in mathematics. The different mathematical operator like division, subtraction, addition, and multiplication holds the inherent capability to explore global maxima and minima. In the proposed research, levy flight-based improved arithmetic optimization algorithm has been proposed for better optimal solutions to various engineering design problems. The fundamental arith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Numerous optimization issues have been addressed by fusing chaotic maps with metaheuristic methods. For instance, in 2023 praveen et al [9] suggested a faster version of the arithmetic method, while in 2017 Arora et al [10] suggested leveraging chaos to enhance the butterfly algorithm. The investigations described above have produced promising experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous optimization issues have been addressed by fusing chaotic maps with metaheuristic methods. For instance, in 2023 praveen et al [9] suggested a faster version of the arithmetic method, while in 2017 Arora et al [10] suggested leveraging chaos to enhance the butterfly algorithm. The investigations described above have produced promising experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the convergence accuracy and convergence speed of AOA are achieved by adopting various mechanisms. For example, Dhawale et al used the Levy flight strategy to enhance the exploitation and exploration capabilities of AOA [ 18 ]. Zhang et al proposed a hybrid AOA algorithm that introduces energy parameters for Harris hawks optimization to balance exploitation and exploration [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 The incorporation of the Levy flight distribution has been found to enhance the performance of optimization algorithms for engineering global optimization problems, leading to improved optimal solutions, as demonstrated in several studies. 27 Additionally, balancing fitness and distance has been shown to enhance the algorithm's capabilities for searching, as reported in various studies. 28 Overall, these findings highlight the potential of incorporating these techniques into optimization algorithms for engineering design problems.…”
mentioning
confidence: 97%